Chicken IgY Fc expressed by Eimeria mitis enhances the immunogenicity of E. mitis. Issue 1 (December 2016) - Qin, Mei; Tang, Xinming; Yin, Guangwen; Liu, Xianyong; Suo, Jingxia; Tao, Geru; EI-Ashram, Saeed; Li, Yuan; Suo, Xun
Abstract Background Eimeria species are obligate intracellular apicomplexan parasites, causing great economic losses in the poultry industry. Currently wild-and attenuated- type anticoccidial vaccines are used to control coccidiosis. However, their use in fast growing broilers is limited by vaccination side effects caused by medium and/or low immunogenicEimeria spp. There is, therefore, a need for a vaccine with high immunogenicity for broilers. Methods The avian yolk sac IgY Fc is the avian counterpart of the mammalian IgG Fc, which enhances immunogenicity of Fc-fusion proteins. Here, we developed a stable transgenicEimeria mitis expressing IgY Fc (Emi.chFc) and investigated whether the avian IgY Fc fragment enhances the immunogenicity ofE. mitis . Two-week-old broilers were immunized with either Emi.chFc or wild typeEimeria and challenged with wild typeE. mitis to analyze the protective properties of transgenic Emi.chFc. Results Chickens immunized with Emi.chFc had significantly lower oocyst output, in comparison with PBS, mock control (transgenicE. mitis expressing HA1 from H9N2 avian influenza virus) and wildtypeE. mitis immunized groups after challenge, indicating that IgY Fc enhanced the immunogenicity ofE. mitis . Conclusions Our findings suggest that IgY Fc-expressingEimeria may be a better coccidiosis vaccine, and transgenicEimeria expressing Fc-fused exogenous antigens may be used as a novel vaccine-delivery vehicle against a wide variety of pathogens.